Boron-Based Compounds for Solid-State Hydrogen Storage: A Review - Yernat Kozhakhmetov; Sherzod Kurbanbekov; Nurya Mukhamedova; Azamat Urkunbay; Aibar Kizatov; Leila Bayatanova; Raushan Nurdillayeva; Dilnoza Baltabayeva (Crystals)
Due to the depletion of hydrocarbon resources worldwide, intensive research is being conducted to identify alternative energy carriers. Hydrogen has emerged as a promising candidate due to its high energy density and environmentally friendly nature. However, large-scale implementation of hydrogen energy is hindered by the lack of safe, efficient, and cost-effective storage methods. Among the various materials studied for solid-state hydrogen storage, boron nitride (BN)-based compounds have attracted significant attention owing to their high thermal stability, tunable morphology, and potential for physisorption-based storage. This review focuses on recent advances in the synthesis, functionalization, and structural optimization of BN-based materials, including nanotubes, nanosheets, porous frameworks, and chemically modified BN. Although other boron-containing hydrides such as LiBH4, Mg(BH4)2, and closo-borates are briefly mentioned for comparison, the primary emphasis is placed on BN-related systems. This paper discusses various modification strategies aimed at enhancing hydrogen uptake and reversibility, offering insights into the future potential of BN-based materials in hydrogen storage technologies.